A turning point for Chinese higher education : developing hybrid education at Tsinghua University - Coates, Hamish, 1974-; Zhang, Yu, 1983-; Li, Manli, 1970-; Zhong, Zhou, 1977- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores how a major Chinese university pivoted to hybrid online and campus education as a result of the COVID-19 pandemic, and the implications of this 'turning point' for Chinese higher education, and also for higher education globally. It looks at how the prolonged disruption has impacted the design of future hybrid arrangements for university teaching. Presented in four parts, the book unpacks Tsinghua's thoughtful yet swift strides into the new era of 'global hybrid higher education.' The book examines influential technology, education, policy, and global forces. It studies transformative leadership which guided change, and construction of extensive and enabling technological infrastructure. Insights from evaluations of student and faculty experiences, interactions, and activities, are accompanied by projections about emerging designs of global hybrid higher education. The research describes future steps for Tsinghua and global universities. Articulating Tsinghua's standing in China and the world, and its contribution to technology and education, this unique research will be of profound interest to students and academics in higher education and education policy and practice, as well as policy experts and higher education leaders around the world"--
Keywords: Qing hua da xue (Beijing, China); Education, Higher -- China; Blended learning -- China; Universities and colleges -- China; Educational change -- China; EDUCATION / Higher